UEG Week 2014 highlights: putting endoscopy into perspective - Papanikolaou, Ioannis S.; Siersema, Peter D. (Endoscopy, 2015)
The 22nd United European Gastroenterology (EUG) Week took place in Vienna in October 2014. The meeting offered a great opportunity to all those interested in gastrointestinal (GI) endoscopy to exchange clinical experiences, research trends, and scientific progress from all over the world. This report will highlight some of the most interesting topics of GI endoscopy that were presented over the 3 days, and will briefly comment on them in light of the latest bibliographic data.